STORY METHOD IN ISLAMIC EDUCATION IN EARLY CHILDREN'S EDUCATION - Syahrir Syahrir; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2019)
The activities and lessons both carried out in the classroom and outside the classroom, and with a variety of methods, such as methods of playing, telling stories, singing and others. Considering the many methods used in the educational process, in this study, the author will limit the problem or focus on the story method in Islamic education the application and influence of story methods in Islamic education implemented and developed in kindergartens in order to form qualified, healthy and skilled children. So what is meant by the title of the story method in Islamic education here is to instill the values of Islamic teachings in the child by using the story method implemented / applied in kindergarten.